Meta-Analysis: The Effect of Diabetes Mellitus Comorbidity on the Risk of Death in Covid-19 Patients - Kun'ain, Utin Ilma Agni; Rahardjo, Setyo Sri; Tamtomo, Didik Gunawan (Indonesian Journal of Medicine, 2020)
Background: Corona Virus Deases 2019 (COVID-19) is an infectious disease caused by the corona virus. COVID-19 is currently a challenge for diabetes patients. Diabetes mellitus predisposes to a very severe disease course and increases the risk of death from COVID-19. This study aims to estimate the average magnitude of the effect of diabetes mellitus comorbidity on the risk of death of COVID-19 patients.Subjects and Method: This was a systematic review and meta-analysis. This research was conducted using secondary data that will be conducted by searching and selecting data from the results of clinical trials conducted around the world. Search for articles through systematic and comprehensive databases from Pubmed, Google Scholar, Springer Link. The analysis in this study was carried out using the Review Manager 5.3 software. The results of the analysis are the effect size, heterogeneity and then the study model. Variations between studies are used to determine the analysis model which is divided into two models, namely the fixed effect model (FEM) and the random effect model (REM).Results: Based on the results of the analysis, there was high heterogeneity between experiments (I2= 85%; p= 0.04), so that the Random Effects Model (REM) was used. COVID-19 patients with comorbid diabetes mellitus were 2.17 times more likely to die than patients without comorbid diabetes mellitus (aOR 2.17; 95% CI 1.04 to 4.54).Conclusion: Diabetes mellitus co-morbidity increases 2.17 times the risk of death in COVID-19 patients compared to patients without diabetes mellitus comorbidity.Keywords: COVID-19, Comorbidity, Diabetes Mellitus, DeathCorrespondence: Utin Ilma Agni Kun'ain. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: utinilmaagni8p@gmail.com. Mobile: +628111044542.Indonesian Journal of Medicine (2020), 05(04): 368-377https://doi.org/10.26911/theijmed.2020.05.04.12.